Inovação Ambiental como Indicador da Boa Governança para o Desenvolvimento Sustentável nos Municípios Cearenses: Um Estudo com Base no Programa Selo Município Verde - Costa, Paulo Henrique Ellery Lustosa da (2017)
During to the 2012 World Summit on Sustainable Development, held in Rio de Janeiro in 2012, good governance of environmental policies was recognized one of the key issues to foster the principles of sustainable development. At the Summit recognized the importance of local governments and local stakeholders on its accomplishment to achieve this goal, in Brazil, environmental authorities were engaged on a long term debate about municipal government capacities to manage local environmental policies as a result of the passing of a piece of law related to that issue (Law 140). Among many important issues there were a couple question demanding to be answered in order the debate to advance: How to identify local governments with institutional capacity for good governance of environmental policies? And how to relate this results do capacity building strategies. This work, based upon a case study on the Green Municipality Award program in the Brazilian state of Ceara from 2004 thru 2012, identifies environmental innovation at local governments as an indicator of good governance and uses quantitative and qualitative analysis to categorize the municipalities of Ceara according to their environmental capacity to innovate. Further than that, the research compares its results to another governance assessment to validate them, achieving a 73,3% matching on relating pioneering on environmental innovation and the stage of local governance of environmental policies.